Correlation between abnormal energy metabolism of ovarian granulosa cells and in vitro fertilization-embryo transfer outcomes in patients with polycystic ovary syndrome and obesity - Ya-Kun Zhao; Ya-Na Gao; Ling-Chao Wang; Jing Wang; Gai-Jing Wang; Hong-Li Wu (BMC, 2023)
Abstract Context Granulosa cells (GCs) that surround oocytes in mammalian reproduction play an active role in oocyte differentiation through proliferation and energy production. Aims This study aimed to investigate the characteristics of the energy metabolism of ovarian GCs and the influence of GCs on the early embryonic development in polycystic ovary syndrome (PCOS). Methods The clinical characteristics and in vitro fertilization-embryo transfer treatment outcomes of 39 patients with PCOS and 68 patients with simple tubal factor infertility who underwent controlled ovarian hyperstimulation were analyzed and summarized. The mitochondrial function and glucose metabolism level of the GCs were determined, as well as the content of oxidative stress markers in the follicular fluid (FF) of patients with and without PCOS. Key results When compared to the non-PCOS group, patients with PCOS had a significantly increased number of retrieved oocytes but a significantly decreased number of high-quality embryos, available embryos, and high-quality blastocyst formation (P < 0.05). Furthermore, the mitochondrial membrane potential, adenosine triphosphate level, and mitochondrial DNA (mtDNA) copy number decreased in the GCs, whereas the levels of reactive oxygen species increased (P < 0.01). The levels of malondialdehyde and 8-oxo-deoxyguanosine (8-OHdG) in the follicular fluid (FF) of the patients with PCOS were higher than those of the control group (P < 0.05), and superoxide dismutase was increased by compensation (P < 0.05). In the PCOS group, the expressions of GLUT1, LDHA, and PFKP were lower than those in the non-PCOS group, and glucose levels were higher. Conclusions The low oocyte competence of PCOS may be associated with mitochondrial dysfunction and abnormal glycolysis. Implications This research offers explanations for the possible connections influencing human ovarian folliculogenesis.